ESG Score and Mutual Fund Performance : Empirical Evidence from India - Soni, Tarun Kumar (Indian Journal of Finance, 2023)
This paper studied the relationship between risk-adjusted returns and ESG disclosures of mutual funds operating in India for 13 years. It tested whether the mutual funds with higher ESG scores generated higher risk-adjusted returns than those with lower ESG scores. Further, it also tested whether the mutual funds with higher ESG scores performed better during the COVID-19 crisis period. After controlling for Fama-French five factors, we found that the performance of mutual funds with higher ESG scores neither generated significant positive alphas during the normal period nor the COVID-19 period. The results pointed toward the higher cost of being socially responsible through higher screening costs, opportunity costs, etc. These findings will interest investors, policymakers, and other stakeholders regarding the perceived advantage of investing in socially responsible mutual funds.